2020
DOI: 10.1002/mrc.4984
|View full text |Cite
|
Sign up to set email alerts
|

Solid state nuclear magnetic resonance studies of hydroxypropylmethylcellulose acetyl succinate polymer, a useful carrier in pharmaceutical solid dispersions

Abstract: Hydroxypropylmethylcellulose (HPMC) acetyl succinate (HPMC-AS) is a key polymer used for the enablement of amorphous solid dispersions (ASDs) in oral solid dosage forms. Choice of the appropriate grade within the material is often made empirically by the manufacturer of small-scale formulations, followed by extensive real time stability. A key factor in understanding and predicting the performance of an ASD is related to the presence of hydrogen (or other) bonds between the polymer and active pharmaceutical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Deconvolution in the carbonyl region of the HPMC-AS polymer reveals two signals assigned to C 15,18 (most shifted peak, S substituent the C Os) and C 13 (A’s C O). 69 The knowledge of the 13 C assignment of both the drug and HPMC-AS polymer plays an important role in the identification of drug–polymer interactions in ASDs as this is largely based on the change in chemical shifts. 4 , 43 The 13 C assignments for the 13 C CP MAS NMR spectra of all ASDs, recorded at less than 1 day at RT/ambient RH, are based on the known spectra of HPMC-AS 69 and acetaminophen form I and II 68 ( Table SI-2 ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deconvolution in the carbonyl region of the HPMC-AS polymer reveals two signals assigned to C 15,18 (most shifted peak, S substituent the C Os) and C 13 (A’s C O). 69 The knowledge of the 13 C assignment of both the drug and HPMC-AS polymer plays an important role in the identification of drug–polymer interactions in ASDs as this is largely based on the change in chemical shifts. 4 , 43 The 13 C assignments for the 13 C CP MAS NMR spectra of all ASDs, recorded at less than 1 day at RT/ambient RH, are based on the known spectra of HPMC-AS 69 and acetaminophen form I and II 68 ( Table SI-2 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The four peaks in the region 105–60 ppm in the spectrum of the HPMC-AS polymer (Figure b) can be attributed to the anomeric C 1 , C 4 , C 2,3 , and C 5,10 carbons, while the shoulders at around 70 and 58 ppm correspond to C 6,9 (CH 2 s) and C 8 (methoxy group), and the three peaks in the aliphatic region to C 16,17 ( C H 2 of the S group), C 14 ( C H 3 of the A group), and C 11 (methyl group of the P moiety). Deconvolution in the carbonyl region of the HPMC-AS polymer reveals two signals assigned to C 15,18 (most shifted peak, S substituent the C Os) and C 13 (A’s C O) . The knowledge of the 13 C assignment of both the drug and HPMC-AS polymer plays an important role in the identification of drug–polymer interactions in ASDs as this is largely based on the change in chemical shifts. , The 13 C assignments for the 13 C CP MAS NMR spectra of all ASDs, recorded at less than 1 day at RT/ambient RH, are based on the known spectra of HPMC-AS and acetaminophen form I and II (Table SI-2).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal assignment of the 1 H and 13 C resonances of HPC in the liquid and solid state were obtained from previous works. [ 15,16 ] The assignment of the solid 13 C and 1 H resonances of HPC is provided in Figure S4.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the establishment of favorable HPC‐drug interactions has been proposed as a basis to rationalize the miscibility and stability of these formulations in the solid state. [ 15 ] Recently, we reported that HPC solubilizing activity in aqueous solutions might be caused by the favorable interplay between HPC chain length and hydration. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%